SCREENING OF SELECTED RICE GENOTYPES FOR IDENTIFICATION OF RESISTANT DONOR LINES AGAINST BROWN PLANTHOPPER, Nilaparvata lugens (Stal) - L. KRISHNA and Y. CHANDRA MOHAN, B. RAGHAVENDER, P. RAJANIKANTH N. R. G. VARMA, S. VANISREE B. VIDYASA (The Journal of Research, PJTSAU, 2021)
Fifty seven rice genotypes were screened following Standard Seedbox Screening Test (SSST), along with two resistant checks (PTB 33 and BM 71) and one susceptible check TN1 to assess the level of resistance to BPH infestation. The study was conducted at Rice Research Station, Hyderabad during 2019-2020.The test revealed that out of 57 rice genotypes, only three genotypes viz., Magic 289, RP 2068-18-3-5 and RNR 28370 exhibited damage score (DS) ranging from 1 to 3 and were designated as resistant (R). Five genotypes viz., Magic-88, Magic-179, IRUE 45, IRUE 52 and RNR 29325 exhibited moderate resistance to BPH. The rest of 49 genotypes, 37 genotypes were identified as moderately susceptible with damage score ranging between 5.1-7.0 while the remaining 12 genotypes were identified as susceptible with damage score of 7.1 to 8.9. Further investigations on the mechanisms of resistance such as antixenosis, antibiosis and tolerance are required to identity the best genotypes that could be used for developing BPH resistant / tolerant variety with desirable yield and quality traits.